Charity: The Divine Science of Allah (SWT) - Dadach, Zin Eddine (Journal of Islam and Science, 2020)
The purpose of this instigation is an attempt to perceive the divine science in nature based on some Quranic verses and a spiritual interpretation of movements in nature. First, based on the Quranic verse (55:7), it is understood that Allah (SWT) urges the regions rich in energy to give part of this richness to the areas poor in energy to create balance and harmony in nature. This is described in this investigation as the first divine law of charity of the Divine Science. From the second Quranic verse (15:21), which is described as the second divine law of charity of the Divine Science, Allah (SWT) also fixes the amount of the matter or energy to be flowing from a rich region to a poor region.  Using the water cycle as an example to sense the divine science, it is perceived that the divine purpose of the oceans is to use solar energy in order to generate a particular flow of water vapor, predetermined by Allah (SWT), as the charity to the dry skies over the seas and oceans. Moreover, the divine duty of the skies over the seas and oceans is to utilize the power of the wind to offer a certain part of that flow of water, predesignated by Allah (SWT), as the charity to the dry skies over the lands. Finally, the divine purpose of the skies over lands is to use the earth’s gravity in order to offer a portion of water as rain or snow, predestined by Allah (SWT), as the charity to the dry land.